Body Image and Social Support as Contributing Factors to the Quality of Life of Breast Cancer Patients - Elliza Puspika Sari; Yulia Indah Permata Sari; Yosi Oktarina (STIKes Patria Husada Blitar, 2025)
Physical changes due to the disease and treatment of breast cancer affect patients' body image and cause significant emotional impacts. Social support is crucial in helping patients cope with these changes, reducing stress, and improving overall quality of life. The aim of the research was to determine the correlation between body image and quality of life, and to assess the relationship between social support and quality of life of breast cancer patients at the Surgical Polyclinic of Raden Mattaher General Hospital Jambi. The research used a quantitative method with a cross-sectional approach. The sample comprised 61 breast cancer patients, obtained by using the Lemeshow formula and purposive sampling method. The research instruments included the Body Image Scale questionnaire, the modified MOS Social Support questionnaire (MSS), and the EORTC-QLQ-BR23 questionnaire. The univariate results showed that the average quality of life score was 56.70 (moderate category), body image had an average score of 24.18 (moderate category), and social support had an average score of 62.80 (moderate category). The bivariate analysis found a correlation between body image and quality of life with a p-value of 0.000 < 0.05 and r = 0.940 and a correlation between social support and quality of life with a p-value of 0.003 < 0.05 and r = 0.371. Nurses can improve patients' quality of life by providing education about physical changes, offering emotional support, referring patients to support groups, and involving families in the healing process.